XXXIII. CONFERENCE OF STUDENT'S SCIENTIFIC ACTIVITY - Palacky University, Medical Faculty of (Biomedical papers, 2000)
Let us introduce the abstracts presented at the XXXIII. Conference of a Student Scientific Activities given annuallyby Medical Faculty of Palacky University in Olomouc and The Medical Students Club. This time it is the very firstchance to present our work in a journal published in English. For a student who is interested and active in a fieldof science this is a great oportunity to show the outcomes of his work. For most of them is was an importantlesson to learn. It is a step-by-step work and on its top there is a standart scientific product. It means that fora majority of students such work as a lecture or an article in the Czech language is more than a common thing.But what a challenge to come up with an expert text in English! Too hard? Unmanageable? Thanks to this greatoportunity we found out that even such situation can be handled. We owe our gratitude to everybody who helpedus on our way. Without helping hands our progress would not be that apparent and without professional supportwe would not face the right direction. Once again - thank you.
Keywords: CONFERENCE OF STUDENT'S SCIENTIFIC ACTIVITY; Olomouc 25 April 2000